The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1533317519848237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2D6 and CYP3A4 Genotypes on the Efficacy of Cholinesterase Inhibitors in Southern Chinese Patients With Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most prevalent form of dementia, and age is strongly associated with the incidence of AD. This study aimed to investigate the association between the genotypes of CYP2D6, CYP3A4, and CYP2C9 genes to the clinical efficacy and tolerability of cholinesterase inhibitors (ChEIs) in Chinese patients with AD. One hundred seventy-nine patients with AD with newly prescribed with ChEIs were recruited. The clinical response and tolerability were evaluated at baseline, 3rd-, 6th-, and 12th-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…However, AD patients with the CYP3A5*1 allele had better clinical outcomes than patients with the CYP3A5*3/*3 allele, but the results were not significant (Magliulo et al, 2011). Another study carried out in Chinese patients with AD also indicated that the CYP3A4 gene does not influence the efficacy of DNP (Ma et al, 2019).…”
Section: Cyp3a4 and Cyp3a5mentioning
confidence: 95%
“…However, AD patients with the CYP3A5*1 allele had better clinical outcomes than patients with the CYP3A5*3/*3 allele, but the results were not significant (Magliulo et al, 2011). Another study carried out in Chinese patients with AD also indicated that the CYP3A4 gene does not influence the efficacy of DNP (Ma et al, 2019).…”
Section: Cyp3a4 and Cyp3a5mentioning
confidence: 95%
“…On the one hand, as an acetylcholinesterase inhibitor (AChEI), Gal is widely used in the treatment of Alzheimer's disease and other dementia (23,24). Previous studies have shown that Gal can improve behavioral flexibility disorder and cortical injury caused by traumatic brain injury (25).…”
Section: I/r Can Cause Oxidative Stress and Energy Metabolismmentioning
confidence: 99%
“…The same finding was confirmed in a study by Ma, which used patients on rivastigmine (the metabolism of which does not pass through CYP2D6) as control group. In the same study, patients carrying the CYP2D6 * 10 allele had significantly fewer adverse effects to donepezil and galantamine (Ma et al, 2019 ). A study by Zhong found that patients with either CYP2D6 * 1/10 or CYP2D6 * 10/10 genotypes had better cognitive responses and higher plasmatic concentration of donepezil at 6 months compared to subjects with CYP2D6 * 1/1; however, there was no significant difference in donepezil concentration between responders and non-responders (Zhong et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…Lastly, it is important to notice that results may be affected by ethnicity and the population studied (Miranda et al, 2017 ). For instance, 37.9% of the Chinese population carries the CYP2D6 * 1 variant, which enhances CYP2D6 activity, and 51.3% carries the CYP2D6 * 10 variant on rs1065852 SNP, which reduces CYP2D6 activity (Lu et al, 2016 ; Ma et al, 2019 ), whereas CYP2D6 * 3, CYP2D6 * 4, and CYP2D6 * 5, which account for 98% of poor metabolizers in Caucasians, only occur in negligible percentages in Chinese patients (Ma et al, 2019 ). In two different studies, Lu et al found that response to donepezil was better in patients with CYP2D6 * 10/10 alleles on rs1065852 SNP (especially if APOE-ε3 non-carriers), and worse in patients with CYP2D6 * 1/10 alleles (Lu et al, 2015 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%